Bromodomain Inhibitors Modulate FcγR-Mediated Mononuclear Phagocyte Activation and Chemotaxis - Banham, Gemma D.; Lee, Colin Y. C.; Ferdinand, John R.; Matthews, Rebeccah J.; Jing, Chenzhi; Smithers, Nicholas; Prinjha, Rab K.; Clatworthy, Menna R. (Frontiers in Immunology, 2022)
IgG antibodies form immune complexes (IC) that propagate inflammation and tissue damage in autoimmune diseases such as systemic lupus erythematosus. IgG IC engage Fcγ receptors (FcγR) on mononuclear phagocytes (MNP), leading to widespread changes in gene expression that mediate antibody effector function. Bromodomain and extra-terminal domain (BET) proteins are involved in governing gene transcription. We investigated the capacity of BET protein inhibitors (iBET) to alter IgG FcγR-mediated MNP activation. We found that iBET dampened IgG IC-induced pro-inflammatory gene expression and decreased activating FcγR expression on MNPs, reducing their ability to respond to IgG IC. Despite FcγR downregulation, iBET-treated macrophages demonstrated increased phagocytosis of protein antigen, IgG IC, and apoptotic cells. iBET also altered cell morphology, generating more amoeboid MNPs with reduced adhesion. iBET treatment impaired chemotaxis towards a CCL19 gradient in IC-stimulated dendritic cells (DC) in vitro, and inhibited IC-induced DC migration to draining lymph nodes in vivo, in a DC-intrinsic manner. Altogether, our data show that iBET modulates FcγR-mediated MNP activation and migration, revealing the therapeutic potential of BET protein inhibition in antibody-mediated diseases.